2020
DOI: 10.3390/su12030783
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Mobility Service Application for Business Travel: Lessons Learnt from a Demonstration Project

Abstract: Business travel contributes to significant greenhouse gas emissions, and there is a need for measures that reduce the demand for trips made with energy-intensive means of transport. In this study, a mobility service application (MSA) introduced in 13 Swedish organisations was tested and evaluated to facilitate booking and handling of business trips, in particular public transport. A before and after study consisting of surveys and interviews with employees at the organisations were conducted. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…With Maximum Likelihood Estimation (MLE) and Bayesian Information Criterion (BIC), [20] leveraged three metrics to analyze the human mobility patterns in two real subway and taxi datasets i.e., trip displacement, trip duration, and trip interval. [21] showed that the mobility service application (MSA) was mostly used for regional and local public transport trips, and the users stated that the MSA made it easier to travel by public transport. [22] showed that psychological needs play a crucial role in the acceptance of MaaS.…”
Section: Analysis On Mobility Behavior and Demand Pattern Of Maas End...mentioning
confidence: 99%
“…With Maximum Likelihood Estimation (MLE) and Bayesian Information Criterion (BIC), [20] leveraged three metrics to analyze the human mobility patterns in two real subway and taxi datasets i.e., trip displacement, trip duration, and trip interval. [21] showed that the mobility service application (MSA) was mostly used for regional and local public transport trips, and the users stated that the MSA made it easier to travel by public transport. [22] showed that psychological needs play a crucial role in the acceptance of MaaS.…”
Section: Analysis On Mobility Behavior and Demand Pattern Of Maas End...mentioning
confidence: 99%
“…In the first two, both the treatment and the control group participated (baseline measurement and trial measurement). The third measurement period was only for the control group's trial period, which was conducted to keep the interest high and prevent dropouts since earlier intervention studies have had such issues [55]. It is also a way of acquiring validation results, although without a control group since no second control group was participating.…”
Section: Data Collection and Trial Proceduresmentioning
confidence: 99%
“…Business trips have a significant impact on the increased demand for transport services. A Swedish study tested the interaction of the application of mobility services with the reservation and implementation of business trips in the context of public transport as well [12]. Part of the provision of transport is also the offer of shared mobility services in urban areas.…”
Section: Introductionmentioning
confidence: 99%